The Effect of Resistance Band Training On The Leg Speed of Badminton Athletes of PB. New Executive (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the Effect of Resistance Band Training on the Foot Speed ​​of Badminton Athletes PB. New Executive. This study refers to a quantitative research approach with an experimental research type using a one-group Pretest-Postest Design research design with a shuttle run test instrument. The population in this study were badminton athletes PB. New Executive, while the sample in this study used total sampling, namely 10 people. The test results showed that there was an effect of training using Resistance Bands on the foot speed of badminton athletes. The hypothesis test showed a value (t count 7.2189> t table 1.833), so that it showed that Ho was rejected and Ha was accepted, which means that there was a significant effect on the foot speed of athletes after being treated with the training method using Resistance Bands.